Normal Curves in 4-Dimensional Galilean Space G4 - Mosa, Safaa; El-Fakharany, Mohamed; Elzawy, Mervat (Frontiers in Physics, 2021)
In this article, Firstly, we give the definition of normal curves in 4-dimensional Galilean space G⁴. Secondly, we give the necessary condition for a curve of curvatures τ(s) and σ(s) to be a normal curve in 4-dimensional Galilean space G⁴. Finally, we give some characterizations of normal curves with constant curvatures in G⁴.